THE ROLE OF SPIRITUAL INTELLIGENCE ON ACHIEVEMENT MOTIVATION - Andriyani, Juli (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2023)
Spiritual Intelligence is vital because it is the highest Intelligence in humans, which includes all the Intelligence that exists in humans. The Intelligence to judge one’s actions or way of life is more meaningful than others. This study aims to determine the relationship between spiritual Intelligence and student achievement motivation at MTsS Babun Najah Banda Aceh. The type of research is quantitative research. The population in this study were MTsS Babun Najah students, a total of 307 people. The Proportionate Stratified Random Sample was used, and obtained a sample of 75 students. The data analysis technique used is correlation analysis and data collection using a Likert Scale Model. The research result showed a relationship between spiritual Intelligence and achievement motivation, meaning that the hypothesis that the researcher proposes is accepted. The correlation analysis showed that spiritual Intelligence with achievement motivation has a positive relationship or correlation with a Pearson Correlation value of 0,640 and a signification value of 0.000, meaning the higher spiritual Intelligence possessed by a person, the higher achievement motivation. Conversely, the lower the spiritual intelligence, the lower the achievement motivation.